Studi Pendidikan Islam Terpadu dalam Pembelajaran Bahasa Inggris - Aco Nasir; Chuduriah Sahabuddin; Abdul Hamid; Ahmad Al Yakin (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
This study aims to produce appropriate teaching materials. This Study is research and development using mix method. It Consists of seven stages, namely(1) planning, (2) initial product development, (3) trials, (4) revisions, (5) field trials, (6) field implementation tests, and (7) final product. The result are(1) Feasibility of assessment of material experts products obtained an average score of 3.58 from all indicator, then an average value of 3.58 was calculated using criteria, then the results were obtained in the Very Good category, while the results Lecturer's Assessment on Product Development was obtained with a total score of 83 out of 19 indicators so that an average of 4.37 was obtained with very good criteria. While the results of the pretest and posttest obtained an average value of 59.3 while the ability after using the development product obtained an average value of 81.98. There is an increase in the average value of 22.68 after using development products based on Islamic values. The gain score obtained by an average of 0.55 from 43 students. Based on the categorization of the results of the gain score analysis, the value of 0.55 is categorized as Medium. It can be concluded that the product developed is effective tobe used in teaching process.